4s-3(-6s-9)=

Simple and best practice solution for 4s-3(-6s-9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4s-3(-6s-9)= equation:


Simplifying
4s + -3(-6s + -9) = 0

Reorder the terms:
4s + -3(-9 + -6s) = 0
4s + (-9 * -3 + -6s * -3) = 0
4s + (27 + 18s) = 0

Reorder the terms:
27 + 4s + 18s = 0

Combine like terms: 4s + 18s = 22s
27 + 22s = 0

Solving
27 + 22s = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 22s = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 22s = 0 + -27
22s = 0 + -27

Combine like terms: 0 + -27 = -27
22s = -27

Divide each side by '22'.
s = -1.227272727

Simplifying
s = -1.227272727

See similar equations:

| a-12=b | | 5z+1=2z+19 | | x-19=29-7 | | 4x-5=18x+2 | | 6+2x=5y-9 | | (x^2-9)(x^2-36)=0 | | (x-3/5)-(1/5)=(x-5/4) | | 2(3x+6)=-40+16 | | B/9-(-45) | | 4/3*3/4 | | 3/2(z+5)-1/4(z+24)-0 | | (20/2)+3=7-2X | | -18=3n+6n | | 0.8x-0.5x-4=8 | | 8n+10/5=26 | | F/3-4 | | -4g+5g-8+4=6g-4 | | 9[3-(-6x-9)]=108x+189 | | x^4-45x+324=0 | | 172/6 | | x+2/3x=35 | | W/9-32=-31 | | (x-6x-7)-(x-7)=2 | | 2x+56=21-8x | | x/(x+7)=3/10 | | 3x^2-414x+11760=0 | | 25+-2f=-21 | | 3x-9-4x=-(5+x) | | 3x+19/5+x+29/4=17 | | 2000+1.50n=12n | | -3x+12=-x+8 | | 2x+37=12 |

Equations solver categories